Pengaruh Brand Image, Brand Trust, Dan Marketing Communication Terhadap Minat Beli Produk Herborist Juice For Skin (Studi Kasus Generasi Z Kota Malang) - Uliya Fadilah; Budi Wahono; Mohammad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Examining the impact of brand image, brand trust, and marketing communication on purchase intention is the goal of this study. This study employed a quantitative research methodology. Purposive sampling is a sort of probability sampling that is employed in the sampling process. Data analysis used SPSS 25 analysis with multiple linear regression techniques. According to the study's findings, brand trust and brand image both significantly influence consumers' propensity to buy impact, as does marketing communication, and brand image, brand trust, and marketing communication all have an impact. on Herborist Juice For Skin products. Keywords: Brand image, brand trust, marketing communication, buying interes